2021
DOI: 10.15403/jgld-2988
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Mortality and Clinical Outcomes in Patients with Acute Diverticulitis in the United States

Abstract: Background and Aims: Diverticular disease represents a leading cause of gastrointestinal-related hospitalizations. We sought to identify the adverse consequences of obesity on acute diverticulitis (AD) hospital admissions. By age 85, approximately two-thirds of individuals will develop diverticular disease and up to 25% will develop AD. Generally, obesity confers an increased risk of morbidity and mortality; however, its impact on hospitalized patients with AD are lacking. Methods: Utilizing ICD-9-CM cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…From a public health perspective, our findings are of paramount importance since overweight is a modifiable risk factor and the observed link may promote a public healthcare policy that identifies individuals with diverticulosis who have an increased risk of experiencing diverticulitis [23]. Recently, Makar et al reported that obesity led to adverse outcomes and several surgical interventions and morbid obesity led to higher mortality rates among patients with acute diverticulitis [24]. Furthermore, recent study by Koziel et al showed that among patients with established coronary artery disease, there was a gradual increase in BMI and waist circumference [25].…”
Section: Discussionmentioning
confidence: 64%
“…From a public health perspective, our findings are of paramount importance since overweight is a modifiable risk factor and the observed link may promote a public healthcare policy that identifies individuals with diverticulosis who have an increased risk of experiencing diverticulitis [23]. Recently, Makar et al reported that obesity led to adverse outcomes and several surgical interventions and morbid obesity led to higher mortality rates among patients with acute diverticulitis [24]. Furthermore, recent study by Koziel et al showed that among patients with established coronary artery disease, there was a gradual increase in BMI and waist circumference [25].…”
Section: Discussionmentioning
confidence: 64%
“…A further issue is that the radiologists reporting on the CTs were all generalists while, ideally, specialist radiologists with similar expertise would have provided reports on the reference values. It could be argued that the actual patient diverticulitis population is not accurately reflected in this study as we excluded obese patients from this study because high-density fat is a limitation to sonographic detection of distinguishable features while obesity is an associated factor for acute diverticulitis [49]. The outcomes in our study reflect a real-world working environment since the scans were carried out by frontline surgeons, either in-training or experienced surgeons on duty, and the post-hoc power of 85% increases our confidence that the results of our study are scalable worldwide.…”
Section: Discussionmentioning
confidence: 99%